The Influence of Leadership and Organizational Culture in Improving Employee Performance in the Department of Food Security, Agriculture and Fisheries of Bekasi City with Work Motivation as a Mediation Variable - Annisa Fauziyyah; Ismail Razak; Mohammad Irawan Noor (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2025)
This study aims to analyze 1). the effect of leadership and organizational culture on work motivation; 2). the effect of leadership and organizational culture on employee performance; 3). the effect of work motivation on employee performance; 4). The effect of leadership and organizational culture on employee performance through work motivation; The research was conducted on employees of the Bekasi City Agriculture and Fisheries Food Security Office with a research sample of 50 respondents. The sampling technique used random sampling technique. The data analysis method uses descriptive analysis and path analysis. The results showed that: 1). there is an influence of leadership and organizational culture on employee work motivation; 2). there is an influence of leadership and organizational culture on employee performance; 3). there is an influence of work motivation on employee performance; 4). there is an influence of leadership and organizational culture on employee performance through work motivation at the Bekasi City Agriculture and Fisheries Food Security Office.